(untitled) (Research, Society and Development, 2025)
The arrest report is the official record through which an arrest in flagrante delicto is registered, documented, and legally justified. In the military context, the drafting of the Military Arrest Report (Auto de Prisão em Flagrante Delito Militar – APFDM) directly impacts the individual’s liberty and requires strict adherence to legal and procedural rules. However, a lack of standardization and technical training has been observed among many officers responsible for this procedure within the Military Police of Alagoas (PMAL). The main objective of this study was to propose the creation of a manual for arrests in military crimes, as well as to emphasize the importance of continuous training for military police and firefighters. The qualitative and deductive methodological approach was developed through bibliographic and documentary research, along with the application of semi-structured questionnaires to PMAL officers. The results indicated that 92.8% had never drafted an APFDM, and 94.6% were unaware of the existence of an institutional manual on the topic. Furthermore, 92.85% of the respondents considered the creation of a specific normative instrument to be necessary. It is concluded that the implementation of a manual will contribute to improving institutional practices, reducing risks of nullity, and strengthening legal security in the handling of military offenses.